Cosa c’è di sbagliato nel modificare la linea germinale? What is wrong with editing the germ-line? (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This work analyses the ethical questions raised by CRISPR-Cas9 technology. CRISPR, which is part of a naturally occurring defense mechanism used by bacteria, has already revolutionized the field of gene editing: it enables scientists to cut the DNA at a precise point and delete, modify or substitute a defective gene in a relatively cheap and quick way, avoiding the manifestation of genetic diseases. However, this technology is extremely controversial, especially with regard to heritable changes in the genome. Our inquiry focuses on the main arguments raised by detractors of germline editing, to clarify the complex interplay of interests linked with genome editing by an ethical and legal perspective.
Keywords: Gene editing; enhancement; human dignity; preimplantation genetic diagnosis; eugenics